KAJIAN PENATAAN PERUMAHAN DAN PERMUKIMAN TEPIAN SUNGAI KAPUAS DI KOTA PONTIANAK (Studi Kasus Kelurahan Tambelan Sampit Kota Pontianak) - Helyanto, -; Mulki, Gusti Zulkifli; Marsudi, - (Fakultas Teknik Universitas Tanjungpura, 2016)
At the beginning of its growth, Pontianak is a city that lived from Kapuas River. One of area in the city of Pontianak that located on the banks of Kapuas River is Tambelan Sampit with an area of 0.41 km2 and the population of 8,037 people (BPS Pontianak, 2016). This area also has several challenges that must be resolved, namely: Lack of public facilities; High building density, irregularity of position, river behind the housing, unqualified building standards and 60% of housing are on the riverbank (Settlement Official of Pontianak, 2015). According to the General Directorate of Coastal and Small Islands in Coastal Guidance (2006), the Coastal City or waterfront city is an area that bordering water and facing the sea, rivers, lakes and the likes. This research aims to provide the concept of housing arrangement and settlement on riverbanks with using qualitative methods. The study and data that obtained was analyzed by triangulation method which is comparing some theories and similar research both from within and outside the country. The conclusion is that buildings should be directed to the riverbank or use a two-faced concept, only open buildings may be developed, reducing building density, building occupants relocated to rusunawa, and rejuvenating the buildings. Suggestions from this research are the arrangement of housing and settlement must also pay attention to local wisdom, as well as the application of strict rules and actions for those who violated the rules. Keywords : Arrangemen, Housing and Settlement, Riverbanks.